PENGUJIAN SISTEM SIPERKA (SISTEM INFORMASI PERPUSTAKAAN KABUPATEN) MENGGUNAKAN METODE USER ACCEPTANCE TESTING - Muhammad Julmawansa Abdullah; Tri Herdiawan Apandi; Erick Febriyanto; Rian Hermawan; Tri Rezqy Maudy; Muhammad Soleh Sulaeman (Jurnal Teknologi Informasi dan Komunikasi, 2026)
Abstract This study aims to analyze the level of user acceptance of the District Library Information System (SIPERKA) using the User Acceptance Testing (UAT) method. SIPERKA was developed to overcome the low achievement of village library data collection in Subang Regency, which is still below 40%. The system was developed using the Laravel 12 framework and web-based technologies, including HTML, CSS, PHP, and JavaScript. The research employed a quantitative descriptive approach. Data were collected through a questionnaire distributed to 14 respondents, using a 5-point Likert scale. User acceptance was evaluated based on five dimensions, namely usability, information quality, system efficiency, user satisfaction, and training quality. The collected data were analyzed using descriptive statistical techniques to determine the mean and standard deviation values. The results indicate that SIPERKA received a positive level of user acceptance, with an overall mean score of 3.94, categorized as Good. The system efficiency dimension achieved the highest mean score (M = 4.14), indicating that the system effectively supports user activities. Furthermore, training quality (M = 3.98), user satisfaction (M = 3.93), information quality (M = 3.86), and usability (M = 3.79) also demonstrated good acceptance levels. In conclusion, the findings show that SIPERKA meets user requirements and is feasible for full implementation. However, improvements in usability are still necessary to enhance system ease of use. This study is expected to contribute to the development and evaluation of web-based library information systems in the public service sector.